(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study the existence of multiple positive periodic solutions for the second order differential equation x''(t) + p(t)x' (t) + q(t)x(t) = f(t, x(t)). By using Krasnoselskii fixed point theorem, we establish some criteria for the existence and multiple positive periodic solutions for this differential equation.